Planning and control software instrument for basketball training educational resources - Macias Garcia Maria, M.; Toledano, M. A. P.; Molina, S. F.; Vegas Maria, M. Á.; Ibanez Godoy, S. J. (International Journal of Computer Science in Sport, 2002)
The planning of training sessions in team sports is generally carried out empirically. The number of pedagogical variables that coaches register during this process is very limited (the description and graphic representation of the exercise). Few bibliographical references mention examples of precise planning that can be extrapolated to different sports modes. Moreover, the existing work only refers to a limited number of variables that are not automated processes. This means that the evaluation and control of the training session is a long and tedious process that rarely occurs. It is necessary to build tools that provide coaches for the planning and control of the pedagogical variables of the training session. The objective of the software presented in this paper is the solving of this problem by offering coaches a systematic register of the planning processes. The registered data will allow the evaluation of the training process and therefore its control.